Cigarette smoke and human pulmonary immune responses to mycobacteria - Van Zyl-Smit, Richard Nellis (Department of Medicine, 2015)
Recent epidemiological evidence suggests that up to 15% of worldwide tuberculosis (TB) cases may be attributable to tobacco smoking. The aim of the studies reported here was to gain insights into the effects of exposure to cigarette smoke on human cells that form part of the innate immune system of host defence in the lung. The experiments on the pulmonary effects of cigarette smoke confirm that exposure has a significant effect upon innate host defences. Significant reductions in the production of key cytokines implicated in defences against mycobacteria were observed, not attributable to impairment of mycobacterial uptake by cigarette smoke extract exposure. Furthermore, control of intracellular mycobacterial growth was impaired by cigarette smoke extract exposure.